Seasonal and Dust‐Related Variations in the Dayside Thermospheric and Ionospheric Compositions of Mars Observed by MAVEN/NGIMS. Issue 11 (8th November 2021) - Yoshida, Nao; Terada, Naoki; Nakagawa, Hiromu; Brain, David A.; Sakai, Shotaro; Nakamura, Yuki; Benna, Mehdi; Masunaga, Kei
Abstract: We report seasonal and dust‐related variations in neutral and ion species (CO2, O, and N2, and CO2 +, O2 +, O +, and N +, respectively) in the dayside Martian upper atmosphere between altitudes of ∼150 and ∼250 km observed by the Neutral Gas and Ion Mass Spectrometer aboard the Mars Atmosphere and Volatile Evolution spacecraft. The sinusoidal seasonal variations in CO2 + and O2 + densities are clearly identified, while that of O + is less discernible. These observed variations in ion densities are well reproduced by a photochemical equilibrium model for CO2 + and O + densities when we combine them with solar cycle variations. Furthermore, we find a decrease in O, O +, and O2 + densities in the whole altitude range at L s = 342–346 in MY 33 during a regional dust event. The decrease in O density would lead to decreases in O + and O2 + densities in the ionosphere through ion‐neutral reactions. Observed variations in ion and neutral species associated with the season and a regional dust storm are also confirmed in pressure coordinates. Observations show that the CO2 + /O + ratio at a given pressure level in the ionosphere varies by a factor of ∼3, which can modify the composition of ion outflow from the Martian atmosphere. Plain Language Summary: Early Mars had a dense CO2 atmosphere that could sustain a significant amount of liquid water, but present Mars only has a 7–9 mbar CO2 atmosphere. Many CO2 gases are considered to have been lost to space. One of the mechanisms for atmospheric escape on Mars is the acceleration of the ion species in the ionosphere by the interaction with the solar wind. Since ionospheric ions can be the source of escaping ions, variability in the number density in the ionosphere might affect the escape rates. The Neutral and Gas and Ion Mass Spectrometer aboard the Mars Atmosphere and Volatile Evolution spacecraft can provide a long‐term data set of number densities and composition in the ionosphere and thermosphere. We investigated the compositional change in number densities in the ionosphere and thermosphere because they are coupled through ion‐neutral reactions. Seasonal variations in neutral and ion densities are observed, and we find that the number densities of O, O +, and O2 + decrease when a regional dust storm occurs in the lower atmosphere. Key Points: Seasonal variations in CO2 + and O2 + in the ionosphere are significant, while those in O + are less discernible The observed variations in CO2 + and O + are well reproduced by a photochemical equilibrium model Decreases in O, O +, and O2 + densities in the thermosphere and ionosphere are found during a regional dust storm